Stolen girl : a novel - Skrypuch, Marsha Forchuk (Scholastic Press, 2019)
When Nadia arrives in Canada in 1950 with Marusia, the woman she calls mother, she is glad to finally be out of the displaced persons camp where she has lived for five years, but troubled by confused memories of World War II; she speaks Ukrainian, but she seems to remember living with a German Nazi family who called her by a different name--and as she tries to settle into the Canadian-Ukrainian community of Brantford she is haunted by one question: who is she, and where was she stolen from?